Análisis de los factores que determinan la sostenibilidad y sustentabilidad de la economía social y solidaria para el cultivo y la comercialización de productos hortofrutícolas en los cantones Quito, Cayambe y Pedro Moncayo - Campos Chicaiza, Alicia Judith (2013)
The application and implementation of the model of the social economy in Ecuador is based legally in Articles 284, 310, 320 and 385 of the Constitution so in this work we make a study of the economic conditions of social responsibility and environmental protection that develops in growing and marketing of horticultural products in the cantons Quito, Cayambe and Pedro Moncayo, processed the information obtained through observation, interviewing and conducting surveys to producers to support the conclusions and project the recommendations in order to contribute to the economic development of the sector